A sustainable approach for removing nitrate: Studying the nitrate transformation and metabolic potential under different carbon source by microorganism. (20th April 2022) - You, Yimin; Chu, Shaohua; Khalid, Muhammad; Hayat, Kashif; Yang, Xijia; Zhang, Dan; Zhou, Pei
Abstract: Excessive nitrate is a critical concern for a long-term greenhouse production system and potentially pollutes groundwater through leaching. Bacillus megaterium NCT-2 can be used to remove excessive nitrate. Enrichments were made from salinized soil, with and without strain NCT-2, to examine the influence of Bacillus megaterium NCT-2 on the nitrate metabolic potential and microbial composition under various carbon sources using detection of nitrogen content, high-throughput sequencing and quantitative real-time PCR. The results demonstrated that strain NCT-2 enhanced the ability of enriched microorganisms to convert nitrate to ammonium with some but not all carbon sources. The microbial composition and their functional potential had a significant relationship with the strain NCT-2 and carbon sources in the concentrates. Specifically, the enrichments with strain NCT-2 significantly increased the relative abundance of Bacillus and Pseudomonas genera, while decreased the relative abundance of Halomonas genus compared to enrichments without NCT-2 strain. Furthermore, in terms of carbon sources, D-cellobiose promoted the enrichment of Enterobacter genus, methyl-glucoside favored the enrichments of Photobacterium or Serratia genera, and D-mannitol favored the enrichments of Photobacterium, Serratia, or Halomonas genera. In summary, the application of Bacillus megaterium NCT-2 will increase the potential of microorganisms to remove nitrate from the environment. Moreover, the current study demonstrates that different carbon sources can also increase the potential for excess nitrate removal by changing the microbial community composition. Graphical abstract: Workflow for assessing the effects of different growing conditions on the microbial population, gene content, and functional activity: 1) Microorganisms of secondary salinized soil were cultured; 2) Enriched culture was inoculated into Eco-biolog plates (different carbon sources culture); 3) Colorimetric analysis was used to determine the OD600, nitrite (NO2 − ), nitrate (NO3 − ), and ammonium (NH4 + ) levels in the culture; 4) DNA was extracted from the microbial community; afterward, 16S rRNA sequencing and q PCR were performed. Image 1 Highlights: The potential of nitrate metabolism by different microorganisms is reported. NCT-2 strain altered microbial composition and function. D-cellobiose and D-mannitol were better with respect to nitrogen species conversion. This study provides a sustainable approach for the removal of excess nitrate.